Feminism: “WAR” and “JOURNEY” Metaphors in Ms. and Bust Magazines - Shi-Fang, Chen; Ting, Su Hie; Chuah, Kee Man (Bilingual Publishing Group, 2025)
As an important medium to spread feminist ideas, magazines have attracted attention in their presentation of feminism. Metaphor analysis helps to understand the public’s cognition and attitude towards social issues, and reveals the role of metaphor in influencing thinking and decision-making. Based on conceptual metaphor theory and using corpus analysis, this paper focuses on feminism-related metaphors in the American magazines Ms. and Bust. Metaphor analysis was conducted for 1,098 articles with 1,664,733 words published from July 1, 2023 to June 30, 2024. Quantitative and qualitative analyses reveal that the “WAR” metaphor and “JOURNEY” metaphor were the top two metaphors related to feminism, yet they encode distinct ideological priorities. The “WAR” metaphor emphasized the plight and struggle women face in opposing gender discrimination and fighting for equal pay and other equal rights, lexicalized through terms like “campaign,” “fight,” and “attacks.” The metaphor of “JOURNEY” highlighted the continuity and development of the feminist movement in the pursuit of political participation and educational equality, lexicalized through terms like “progress,” “ways,” and “course.” This study contributes to existing literature by uncovering the metaphorical patterns of feminism in the American women’s magazines and providing novel perspectives on the understanding of American feminist movement, as well as a useful reference for related research and gender equality practice.